Analysis of the Financial Performance Implications for Establishing an Ecosystem State-Owned Holding in Indonesia - Dewi, Tri Kartika; Wulandari, Permata (Eduvest - Journal of Universal Studies, 2025)
This research examines differences in financial performance resulting from the establishment of Indonesia's State-Owned Holding (SOH) by comparing the periods before and after its formation. While many countries have adopted centralized SOH models, the effect on State-Owned Enterprise (SOE) performance under SOH remains unclear. This case study employs a mixed-method approach, incorporating secondary data analysis of quarterly financial reports from six holding members from 2018-2023, alongside primary data obtained from in-depth interviews with five CFOs in the State-Owned Member Holding and relevant government stakeholders. Descriptive statistics and the Wilcoxon Signed-Rank Test were used to identify differences in financial performance before and after the establishment of the holding. In parallel, qualitative analysis was conducted to explore the underlying factors influencing financial outcomes. The research findings reveal that the formation of the holding has not uniformly improved the financial performance of all members in pre- and post-holding financial metrics in profitability indicators (ROE, ROA), liquidity (Quick Ratio), and leverage (DER). Interview results suggest that the timing of the holding's formation—during the COVID-19 pandemic—and the varying initial financial conditions of member entities, due to corporate actions prior to integration, played significant roles. Additionally, some members faced constraints in accessing bank facilities and were burdened with government assignments for economic and social objectives. Results are consistent with prior studies, which highlight that the performance of SOEs under SOH may deteriorate when government intervention persists, particularly when driven by non-commercial, social objectives.